Study on the relationships between cohesion and coupling metrics on fault prediction in object oriented systems - Domingos, Samuel António Miquirice (2018)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2018.